Analisis Rasio Likuiditas Dan Solvabilitas Dalam Menilai Kinerja Keuangan Pada PT. Sentra Food Indonesia Tbk - Adisti Wulandari; Ocha Ananda; Ratih Kusumastuti (JURNAL MANAJEMEN DAN BISNIS EKONOMI, 2023)
The purpose of this study is to determine the financial performance of PT Sentra Food Indonesia Tbk for the period 2018-2022 as measured by the Liquidity to Solvency Ratio. The source used in this research is the financial statements of PT Sentra Food Indonesia Tbk 2018-2022. The analysis method used in this research is descriptive statistical analysis method. The liquidity level of PT is determined from the results of data analysis. The current ratio of PT Sentra Food Indonesia Tbk averaged 74.93% at the current level from 2018 to 2022, which is below the industry standard of 200%, putting the company in good condition. This indicates low liquidity. PT Sentra Food Indonesia Tbk's quick ratio averaged 46.67% over the 2018-2022 period, below the industry standard of 150%, indicating a loss. The solvency level of PT Sentra Food Indonesia Tbk based on the average debt to assets ratio from 2018 to 2022, is at 52.53%, higher than the industry standard of 35%, indicating a poor situation. For the debt to equity ratio of PT Sentra Food Indonesia Tbk from 2018 to 2022 is 116.18%, higher than the industry standard of 66%, indicating that the situation is not good.